The (God-) man on the Mountain: The Christology of the Transfiguration - Kibbe, Michael H. (Pro ecclesia, 2024)
The transfiguration of Jesus is undoubtedly one of the strangest moments in his earthly sojourn, and the volume of literature on it is reflective of its oddity as well as its importance. But nearly all of that literature focuses on various exegetical or canonical issues, sometimes to the detriment of sufficient attention on the main point: the revelation of Jesus himself. This essay unpacks the identity of Jesus on the mountain, paying special attention to the relative importance of Jesus’ deity and humanity in that glorious moment.